2011
DOI: 10.3945/jn.111.143347
|View full text |Cite
|
Sign up to set email alerts
|

Higher Intakes of Energy and Grain Products at 4 Years of Age Are Associated with Being Overweight at 6 Years of Age

Abstract: This study examined dietary factors associated with overweight in a population-based sample of 6-y-old children. Analyses of data from the Québec Longitudinal Study of Child Development (QLSCD) included a representative sample (n = 1014) of children born in 1998 in the province of Québec, Canada. Dietary intake was measured by using a 24-h dietary recall administered at 4 y of age. Weight and height were measured using a standard protocol at 6 y. Using logistic regression, higher daily energy intake at 4 y was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Furthermore, cross-sectional studies from other countries have suggested that EI is positively associated with BMI z -scores in 2–9 year old European children [ 9 ], whilst not associated with BMI or waist circumference in children aged 5–17 years in Australia [ 11 ]. In prospective studies, higher daily EI at 4 years of age was found to be significantly related to being overweight at 6 years of age in Canadian children [ 12 ]; however, the association was not found in 8 year old Italian children in a 4 year follow up [ 13 ]. We speculate that these inconsistent findings are likely due to different ethnicities, economic status, and social environments between countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cross-sectional studies from other countries have suggested that EI is positively associated with BMI z -scores in 2–9 year old European children [ 9 ], whilst not associated with BMI or waist circumference in children aged 5–17 years in Australia [ 11 ]. In prospective studies, higher daily EI at 4 years of age was found to be significantly related to being overweight at 6 years of age in Canadian children [ 12 ]; however, the association was not found in 8 year old Italian children in a 4 year follow up [ 13 ]. We speculate that these inconsistent findings are likely due to different ethnicities, economic status, and social environments between countries.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is known to occur as a result of genetic, environmental, life style and behavioral influences [ 8 ]. Dietary energy intake (EI) is a major environmental risk factor which has been the focus of numerous studies of European [ 9 ], American [ 10 ], Australian [ 11 ], Canadian [ 12 ], Italian [ 13 ] and Chinese children [ 14 ]. However, described associations of dietary EI with child body composition have been inconsistent in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods are expensive and often not feasible. An alternate approach adopted by several national surveillance surveys ( 28 – 30 ) is to flag missing meal data and conduct follow-up interviews with childcare providers. However, Briefel et al ( 31 ) showed that enhancing parent-reported recalls with other caregiver reports produced results similar to those of unenhanced protocols (1,159 kcal/day±28.5 vs. 1,131 kcal/day±33.5).…”
Section: Discussionmentioning
confidence: 99%
“…We have chosen to administer one 24-hour dietary recall at each time point to assess children’s diet as a secondary outcome so as to not overburden mothers with questionnaires and also because the National Cancer Institute’s latest recommendations [50] support the single administration of 24-hour dietary recall to assess change in mean usual intake of a food group between two points in time. The collection of food data by a 24-hour dietary recall has been considered as an appropriate approach with children in previous studies and national nutrition surveys [5,58,59]. …”
Section: Methodsmentioning
confidence: 99%